Youth Challenge; the Awareness of Healthcare Education in Prevention of Adolescent Pregnancy (International Journal of Scientific Research and Management (IJSRM), 2025)
Adolescents face various physical and psychological changes due to their rapid growth and development. Therefore, adolescent pregnancy causes to many physical, psychological and social problems. To determine the impacts of peer influence, socio economic status, knowledge of sexually transmitted diseases (STD) and knowledge of safety measures of pregnancy towards awareness of healthcare education related to adolescent pregnancy were objectives of this study. Advanced level girls of Sri Lankan schools are aimed population and sample of 373 was collected by validated questionnaire as per stratified sampling method. According to the results, students live in moderate to low socio-economy; moderate to high peer influence; moderate to low knowledge of safety measures of pregnancy; moderate to high knowledge of STI; moderate to high awareness of healthcare education related to adolescent pregnancy. The study finding revealed a positive outcome towards awareness of healthcare education related to adolescent pregnancy from knowledge of STI, knowledge of safety measures of pregnancy and peer influence. But there was no significant impact from socio-economic status to awareness of healthcare education related to adolescent pregnancy. The results were proved by pilot study of adolescent pregnant ladies and can be concluded that awareness of healthcare education can be developed through knowledge of STI, knowledge of safety measures of pregnancy with support of peer influence for prevent adolescent pregnancy. Therefore, conducting comprehensive sex education programs in schools, community intervention programs focusing on teenagers and ensuring general access of contraceptives to enhance awareness of healthcare education will be beneficial to eliminate adolescent pregnancy.